2022
DOI: 10.3390/biomedicines10020208
|View full text |Cite
|
Sign up to set email alerts
|

Induced Pluripotent Stem Cells for Treatment of Alzheimer’s and Parkinson’s Diseases

David A Yefroyev,
Sha Jin

Abstract: Neurodegenerative diseases are a group of debilitating pathologies in which neuronal tissue dies due to the buildup of neurotoxic plaques, resulting in detrimental effects on cognitive ability, motor control, and everyday function. Stem cell technology offers promise in addressing this problem on multiple fronts, but the conventional sourcing of pluripotent stem cells involves harvesting from aborted embryonic tissue, which comes with strong ethical and practical concerns. The keystone discovery of induced plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 80 publications
(122 reference statements)
0
15
0
Order By: Relevance
“…Specifically, numerous studies have demonstrated that iPSCs and ESCs are molecularly and functionally equivalent, avoiding the ethical issues and the constraints of traditional methods. This provides a meaningful solution for a sustainable source of pluripotent stem cells without the need for immunosuppressive agents to combat immune rejection after implantation therapy (Yefroyev and Jin, 2022). Similar to ESCs, iPSCs show selfrenewal ability and multi-directional differentiation potential.…”
Section: Treatment Of Parkinson's Disease Based On the Interaction Of...mentioning
confidence: 99%
“…Specifically, numerous studies have demonstrated that iPSCs and ESCs are molecularly and functionally equivalent, avoiding the ethical issues and the constraints of traditional methods. This provides a meaningful solution for a sustainable source of pluripotent stem cells without the need for immunosuppressive agents to combat immune rejection after implantation therapy (Yefroyev and Jin, 2022). Similar to ESCs, iPSCs show selfrenewal ability and multi-directional differentiation potential.…”
Section: Treatment Of Parkinson's Disease Based On the Interaction Of...mentioning
confidence: 99%
“…A few other recent studies have also expanded our understanding of viral infections and the associated neurological complications. iPSC- derived cells can be used as 2D and 3D cultures for CNS disease modeling, phenotypic assays, neural differentiation analysis, functional characterization, and cell migration studies, as well as cell therapies [ 253 , 254 , 255 , 256 , 257 ]. The potential of 3D brain organoids, derived from iPSCs, to replicate the CNS cell networks, shedding light on infections like HIV-1, HSV-1, and SARS-CoV-2 has been described [ 258 ].…”
Section: The Use Of Ipsc-derived Cells In Neuroinflammatory Disease P...mentioning
confidence: 99%
“…Clinical trials using iPSCs are still rare and not yet being applied in AD, although there are some studies on Parkinson’s disease [ 193 , 194 , 195 , 196 ]. Progress in using stem cells in humans is slowed by the disadvantages, such as the need for immunosuppression and the risk of tumor formation with progenitor cells [ 165 ].…”
Section: Stem Cellsmentioning
confidence: 99%